ANALISIS BENTUK PERUNDUNGAN VERBAL PADA SISWA KELAS TINGGI DAN STRATEGI PENANGANAN GURU DI SD NEGERI 68 PEKANBARU - Nurmailis; Neni Hermita; M. Jaya Adi Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the forms of verbal bullying occurring among upper-grade elementary students and the strategies employed by teachers to address these incidents at SD Negeri 68 Pekanbaru. The research used a qualitative approach with a case study design. Data were obtained through in-depth interviews with homeroom teachers, classroom observations, and supporting documentation. The findings reveal that the dominant forms of verbal bullying include physical mockery, negative labeling, insulting remarks related to academic abilities, and intimidating verbal threats. These behaviors commonly occur during daily interactions inside the classroom and on the school grounds, often unnoticed by teachers due to their quick and subtle nature or because they are perceived as ordinary peer interactions. Teachers’ handling strategies consist of both preventive and corrective efforts. Preventive actions include strengthening students’ empathy, establishing classroom rules, fostering positive communication habits, and integrating character education into daily activities. Corrective strategies involve direct mediation between perpetrators and victims, classroom-based counseling, and collaboration with parents to follow up on repeated behaviors. However, teachers still face challenges such as limited time, insufficient professional training on bullying response, and a school culture that is not yet fully responsive to bullying issues. This study highlights the need for enhanced teacher training and reinforced school policies to prevent and manage verbal bullying more effectively and systematically.